2009
DOI: 10.1002/jmor.10733
|View full text |Cite
|
Sign up to set email alerts
|

The colonic groove or furrow: A comparative morphological study of six species of African mole‐rats (Rodentia, Bathyergidae)

Abstract: Herbivorous mammals such as nutrias, guinea pigs, chinchillas, and mole-rats have a longitudinal mucosal colonic groove (furrow) in their ascending colon, which is thought to play a role in the colonic separation mechanism (CSM). It is not known whether this groove is structurally modified to adapt to this function in mole-rat species. The morphology of this groove was studied in 32 mol-rats, four species, one of which consisted of three subspecies, endemic to southern Africa and two species found in eastern A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 15 publications
2
18
1
Order By: Relevance
“…Having a CSM has been associated with coprophagy (Björnhag & Snipes, ), which has been reported in H. emini , but not T. splendens . The colonic groove in T. splendens was narrow and nonpapillated and was similar to the delicately papillated groove described in another East African mole‐rat species, namely H. glaber (naked mole‐rat; (Kotzé, Van der Merwe, Ndou, O'Riain, & Bennett, ). The histological structure of the colonic groove was similar to H. glaber where the mucosa of the colonic groove and its ridges were similar to that of the rest of the colon.…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…Having a CSM has been associated with coprophagy (Björnhag & Snipes, ), which has been reported in H. emini , but not T. splendens . The colonic groove in T. splendens was narrow and nonpapillated and was similar to the delicately papillated groove described in another East African mole‐rat species, namely H. glaber (naked mole‐rat; (Kotzé, Van der Merwe, Ndou, O'Riain, & Bennett, ). The histological structure of the colonic groove was similar to H. glaber where the mucosa of the colonic groove and its ridges were similar to that of the rest of the colon.…”
Section: Discussionsupporting
confidence: 72%
“…glaber where the mucosa of the colonic groove and its ridges were sim-ilar to that of the rest of the colon. The colonic groove of H. emini resembled that of Georychus capensis (Cape mole-rat) in that the groove walls were low ridges and was wide in the proximal colon and narrowed as it progressed to the distal colon (Kotz e et al, 2009). However, the papillae were not as robust as described in the other Bathyergidae, but was more delicate and similar to that observed in H. glaber Similar V-shaped mucosal folds to those observed in T. splendens have been observed in insectivorous rodents Acomys spinosissimus (Southern African spiny mouse) (Boonzaier et al, 2013) and Jaculus jaculus (Lesser Egyptian jerboa) (Pereira et al, 2016), but not reported in other African mole-rat species (Kotz e et al, 2010).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations